2018
DOI: 10.1021/acssuschemeng.8b04773
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Facile Pretreatments of Bagasse for Efficient Enzymatic Conversion and Their Impacts on Structural and Chemical Properties

Abstract: Novel and sustainable pretreatment approaches are desired to improve the techno-commercial feasibility of biorefineries in the future. In this study, 10 renewable deep eutectic solvents (DESs) were evaluated for their pretreatment efficiency at facile conditions with sugar cane bagasse as substrate and compared with conventional pretreatment approaches (dilute alkali, dilute acid, and ionic liquid (IL)) for lignin removal, saccharification yield, cellulose accessibility, crystallinity, and physiochemical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(14 citation statements)
references
References 62 publications
(144 reference statements)
0
12
0
Order By: Relevance
“…Furthermore, the extent of delignification in the obtained CR processed in different DES compositions seems to have no direct correlation with the glucose yields obtained [delignification DPCR10 = 56.0 ± 2.14%; DPCR20 = 67.9 ± 4.62% at 95.9 ± 2.12% and 92.5 ± 1.63% glucose yield, respectively]. Indeed, several papers report high glucose yield (~90%) with 50–60% delignification 17 , 51 , 52 , even 91% glucose yield at ~10% delignification 53 . Therefore, we believe that the formation of condensed lignin particles, in analogy to the previously reported inhibiting effect of redeposited pseudolignin 54 56 , is the reason for decreased enzyme activity.…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, the extent of delignification in the obtained CR processed in different DES compositions seems to have no direct correlation with the glucose yields obtained [delignification DPCR10 = 56.0 ± 2.14%; DPCR20 = 67.9 ± 4.62% at 95.9 ± 2.12% and 92.5 ± 1.63% glucose yield, respectively]. Indeed, several papers report high glucose yield (~90%) with 50–60% delignification 17 , 51 , 52 , even 91% glucose yield at ~10% delignification 53 . Therefore, we believe that the formation of condensed lignin particles, in analogy to the previously reported inhibiting effect of redeposited pseudolignin 54 56 , is the reason for decreased enzyme activity.…”
Section: Resultsmentioning
confidence: 95%
“…Proton-catalyzed cleavage of chemical bonds was one of the main pathways of lignin removal from biomass, which was why most acidic systems performed well . Because acidity could describe the main characteristics of acids, this section explored the effect of acidity of HBDs on biomass delignification.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, according to the literature on the treatment of bagasse with DESs, L-DES is used to dissolve lignin in the residue after alkaline pretreatment. This work could obtain the highest removal rate of lignin according to the existing studies on lignin removal from bagasse with DESs treatment [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hou et al [ 5 ] found that the ester bond of the linkage between lignin and hemicellulose was broken from the infrared of lignocellulose treated with DESs, the hydrogen bond of the linkage between hemicellulose and cellulose was broken, and hemicellulose was hydrolyzed into oligosaccharides dissolved in DESs. Many studies have shown that DESs can be used as an effective solvent for the lignin separation of bagasse lignin, cellulose, and hemicellulose fractions, with a lignin removal of up to 81% [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%